دور المشرع والقاضي في إعادة التوازن المالي للعقد - أ.د سي يوسف / كجار زاهية حورية (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
The contract is the most efficient way to allow contractors to achieve their objectives and to guarantee access to various services and products, whether they are intended for personal, family or professional consumption. But this can only be done if this contract is validly formed with its elements and conditions, namely the offer and the acceptance, taking into account the requirements of the law, in particular the form, the capacity and the respect of the public order. Thus, it is binding on the parties, because it cannot be terminated or modified to give effect to the principle of the binding force of the contract. Since the contract is the most widely used tool for building relationships and a means of obtaining goods and services - as stated above - However its traditional principles - including the principle of binding force of contract - have failed to achieve a balance between its parts due to the economic and technological transformations that society has undergone, which necessitated the intervention of the legislator and the judge to limit the abuse of this principle in order to restore balance between the contracting parties and thus achieve contractual justice.